The Effect of E-Worksheets With The Problem Based Learning Model Assisted by PhET on Global Warming Material on Critical Thinking Skills - Aditya, I Made; Viyanti, Viyanti (Universitas Muhammadiyah Purworejo, 2025)
The purpose of this study is to investigate the effect of students' critical thinking skills in relation to the issue of global warming when using Problem-Based Learning (PBL) e-worksheets assisted by PhET. Students from classes X2 and X4 participated in this study, which was conducted at SMA Negeri 1 Seputih Raman during the odd semester of the 2023/2024 academic year. In this non-equivalent control group research design, the dependent variable is critical thinking skills, the moderator variable is the PBL model, and the independent variable is the PBL-based e-worksheet assisted by PhET. The study results indicate that the use of PBL-based e-worksheets assisted by PhET enhances students' critical thinking skills. This is confirmed by the n-gain test results, which show that the control class obtained a low score of 0.299, while the experimental class achieved a moderate score of 0.498. Additionally, the effect size test produced a score of 1.78, which falls into the very high category. In conclusion, compared to traditional video-based worksheets, PBL-based e-worksheets assisted by PhET have been proven to be significantly more effective in improving students' critical thinking skills.